Biopsy-derived organoids in personalised early breast cancer care: challenges of tumour purity and normal cell overgrowth cap their practical utility - Schwerd-Kleine, Paul Albert Wolfgang; Würth, Roberto; Cheytan, Tasneem; Michel, Laura L.; Thewes, Verena; Gutjahr, Ewgenija; Şeker-Cin, Huriye; Kazdal, Daniel; Neuberth, Sarah-Jane; Thiel, Vera; Schwickert, Jonas; Vorberg, Tim; et al. (International journal of cancer, 2025)
The ability to establish organoids composed exclusively of tumour rather than healthy cells is essential for their implementation into clinical practice. Organoids have recently emerged as a powerful tool to expand patient material in culture and generate modifiable 3D models derived from humans or animal models. For translational research, they enable the creation of model systems for an ever-increasing number of cell types and diseases. And in personalised medicine, they potentially allow for functional drug testing with high predictive power in certain settings. We found that using biopsy material from untreated, early-stage primary breast cancer patients poses significant challenges for consistently culturing tumour cells as organoids. Specifically, we observed frequent outgrowth of genetically normal, non-cancerous epithelial cells. We analysed >100 biopsy samples from early-stage breast cancer and present our large collection of >70 organoid lines. We also show methods of assessing successful tumour cell culture in a time, and cost-efficient manner, proving a high rate (>85%) of normal cell overgrowth in early-stage breast cancer organoids. Finally, we show a number of successful attempts to culture cancer organoids from mastectomy-derived tissue of advanced, metastatic breast cancer. We conclude that the usefulness of organoids from early breast cancer for translational research and personalised medicine, especially guidance of adjuvant or post-surgical maintenance therapy, is strongly limited by the low success rate of culturing cancerous cells under organoid conditions.
Gesehen am 25.07.2025